The symbolism of the winged disk in the artistic scenes of the Neo- Assyrian Period (911-612 BC). (Damascus University Journal of Historical Studies, 2025)
This research is concerned with studying one of the prominent artistic symbols in the Neo-Assyrian artistic scenes (911-612 BC), which is the winged disk. Unlike the winged disk, which was used by the Babylonians as a symbol of the sun god Shamash, researchers assume that the winged disk was used by the Assyrians as a symbol of another god, the god Ashur, the supreme god of the Assyrians, who appears in Assyrian artistic scenes within the central component of the winged disk. The research aims to evaluate the hypothesis linking the winged disk with the god Ashur in Neo-Assyrian artistic scenes. The results show that the Assyrians used the winged disk as a symbol of the sun god Shamash at times and as a symbol of the god Ashur at other times. On the other hand, the image of the god that appears within the central component of the winged disk does not always represent the god Ashur, as some of these images also represent the god Shamash. In artistic scenes in which the image of the god within the central compmenet of the winged disk symbolizes the god Ashur, this god has some of the characteristics of the god Ninurta.
Keywords: Winged disk; The god Shamash; The god Ashur; Rock reliefs